Scenes from the suburbs : suburban space in US film and television - Vermeulen, Timotheus (Edinburgh University Press, 2014)
This is a study of the representation of suburban space in US film and television. Suburbia. Say the word and a stream of images pass before your eyes: white picket fence, neatly mowed lawns, winding roads nicely lined with trees, pastel tinted bungalows, bored housewives, conspicuous consumption. We all know what the suburbs are about. Or do we? This book looks again at the filmic and televised spaces we think we know so well. How are these spaces built up? What is it that makes us recognize them as suburbs? How do they function? Exploring the hometowns of, amongst others, Desperate Housewives, The Simpsons, Pleasantville and Brick, Scenes from the Suburbs examines what it means to be suburban today. It focuses exclusively on cinematic and televisual representations of US suburbs. It uses the lens of the suburb to view canonical films and television programmes in a completely different light. It integrates theory and close textual analysis to come to a new understanding of the construction of visual landscapes.